2005
DOI: 10.1152/jn.01275.2004
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Purkinje Cell Single-Unit Activity and Simultaneously Recorded Field Potentials in the Immediately Underlying Granule Cell Layer

Abstract: Lu, Huo, Mitra J. Hartmann, and James M. Bower. Correlations between Purkinje cell single-unit activity and simultaneously recorded field potentials in the immediately underlying granule cell layer. J Neurophysiol 94: 1849 -1860, 2005. First published May 31, 2005 doi:10.1152/jn.01275.2004. Evidence from both anatomical and physiological studies suggests that the ascending segment of the granule cell axon provides a large, driving input to overlying Purkinje cells. In the current experiments, we used dual rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 63 publications
3
46
1
Order By: Relevance
“…T and C corresponded to the trigeminal and cortical responses previously observed in Crus-IIa (Bower and Woolston, 1983;Morissette and Bower, 1996) (L. Roggeri and E. D'Angelo, unpublished observations). The D (delayed) wave was not reported previously [but see Lu et al (2005), their Fig. 7] and may correspond to signals elaborated in brainstem circuits (Kleinfeld et al, 1999;O'Connor et al, 2002).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…T and C corresponded to the trigeminal and cortical responses previously observed in Crus-IIa (Bower and Woolston, 1983;Morissette and Bower, 1996) (L. Roggeri and E. D'Angelo, unpublished observations). The D (delayed) wave was not reported previously [but see Lu et al (2005), their Fig. 7] and may correspond to signals elaborated in brainstem circuits (Kleinfeld et al, 1999;O'Connor et al, 2002).…”
Section: Resultsmentioning
confidence: 65%
“…The exposure of the cerebellar surface was performed following surgical procedures reported previously (Bower and Woolston, 1983;Morissette and Bower, 1996;Lu et al, 2005). Briefly, after the skin and muscles were dislocated (during this phase, cutaneous reflexes were reduced with 0.2 ml of lidocaine; AstraZeneca) and the bone was cleaned, a 0.5 mm hole was drilled 2-3 mm posterior and 3-4 mm lateral from lambda on the left hemisphere to expose the cerebellar surface in correspondence to Crus-IIa.…”
Section: Methodsmentioning
confidence: 99%
“…Axons from granule cells ascend to the ML synapse with PCs during the ascent and bifurcate to form parallel fibers (Huang et al 2006;Tolbert et al 2004). Stimulating mossy fibers activates a local patch of PCs via ascending axons of granule cells (Bower and Devor 2003;Cohen and Yarom 1998;Rokni et al 2007), as shown by correlated activity of granule cells and their overlying PCs (Lu et al 2005). Similar patches of Cb activation were observed during tactile stimulation (Bower and Woolston 1983) in intact rats.…”
Section: Responses To Granule Cell Layer Microstimulation Maymentioning
confidence: 71%
“…In the LTP channel, the delay is reduced and the average frequency of granule cell discharge is enhanced, whereas the opposite happens in the LTD channel (Nieus et al, 2006). By doing so, the LTP (or LTD) channels could favor (or prevent) the activation of specific Purkinje cell and molecular layer interneuron assemblies (Bower, 2002;Lu et al, 2005) as well as the development of short-term (Isope and Barbour, 2002;Sims and Hartell, 2005) and long-term synaptic plasticity (Hansel et al, 2001;Casado et al, 2002) at the corresponding parallel fiber synapses.…”
Section: Discussionmentioning
confidence: 99%